2023
DOI: 10.3390/life13071455
|View full text |Cite
|
Sign up to set email alerts
|

New Biomarker Combination Related to Oxidative Stress and Inflammation in Primary Open-Angle Glaucoma

Abstract: Glaucoma is a multifactorial neurodegenerative disease and the second leading cause of blindness. Detection of clinically relevant biomarkers would aid better diagnoses and monitoring during treatment. In glaucoma, the protein composition of aqueous humor (AH) is relevant for the discovery of biomarkers. This study analyzes AH protein concentrations of putative biomarkers in patients with primary open-angle glaucoma (POAG) compared to a control group. Biomarkers were selected from known oxidative-stress and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…We previously reported the axonal-protective effects of ripasudil in a tumor necrosis factor (TNF)-induced axonal damage model [ 7 ] and demonstrated the axonal-protective effects of brimonidine in the TNF-induced axonal damage model [ 8 ]. There have been several recent reports showing a close relationship between TNF and glaucoma [ 9 , 10 ]. Those associations are supported by previous studies showing that increased expression of TNF and TNF receptors were observed in RGCs and the optic nerve head of patients with glaucoma [ 11 ] and that TNF-mediated cell death is involved in the neurodegeneration process of glaucoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the axonal-protective effects of ripasudil in a tumor necrosis factor (TNF)-induced axonal damage model [ 7 ] and demonstrated the axonal-protective effects of brimonidine in the TNF-induced axonal damage model [ 8 ]. There have been several recent reports showing a close relationship between TNF and glaucoma [ 9 , 10 ]. Those associations are supported by previous studies showing that increased expression of TNF and TNF receptors were observed in RGCs and the optic nerve head of patients with glaucoma [ 11 ] and that TNF-mediated cell death is involved in the neurodegeneration process of glaucoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…POAG pathophysiology [ 5 ] determines the state-of-art biomarkers residing in the aqueous humor or the trabecular meshwork, as well as the optic nerve and peripheral blood [ 6 ]. These molecular markers dictate the extracellular matrix status and define cell-signaling or stress molecules and immune surveillance.…”
Section: Introductionmentioning
confidence: 99%